2002
DOI: 10.1109/tsm.2002.804872
|View full text |Cite
|
Sign up to set email alerts
|

Particle adhesion and removal mechanisms in post-CMP cleaning processes

Abstract: Chemical mechanical polishing (CMP) is considered as the paradigm shift that enabled optical photolithography to continue down to 0.12 m. Currently, the polishing physics is not well defined though it is known that the nature of the process makes particle removal after CMP difficult and necessary. It is important to understand the particle adhesion mechanisms resulting from the polishing process and the effect of the adhering force on particle removal in post-CMP cleaning processes. In this paper, strong parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 7 publications
1
68
0
Order By: Relevance
“…The microspheres should be dry when they are applied to the coverslip. We find that microspheres deposited on a coverslip directly from a solution (water or acetone) cannot be launched [62,63].…”
Section: Launching Microspheresmentioning
confidence: 92%
“…The microspheres should be dry when they are applied to the coverslip. We find that microspheres deposited on a coverslip directly from a solution (water or acetone) cannot be launched [62,63].…”
Section: Launching Microspheresmentioning
confidence: 92%
“…Busnaina et al [30] found that full contact between a brush and a particle is necessary to lift or roll particles smaller than 0.1 mm off a substrate.…”
Section: Brush Cleaningmentioning
confidence: 99%
“…30 AFM images of the copper surface after polishing in (a) a DI water based alumina slurry, (b) a DI water based silica slurry, (c) a citric acid-based alumina slurry, and (d) a citric acid based silica slurry at pH 6.…”
mentioning
confidence: 99%
“…The velocity profile between the substrate surface and the brush surface is usually assumed to be linear for simplicity [1][2][3]. However, the flow field comprised by the substrate and brush actually form a thin layer fluid flow because the brush usually is located very close to the wafer surface to generate a larger drag force.…”
Section: Drag Forcementioning
confidence: 99%
“…The currently used post-CMP cleaning techniques include brush scrubbing [1][2][3], ultrasonic and megasonic cleaning [4], fluid jet cleaning [5], laser heating [6] and chemical dissolution [7]. All of these techniques have practical limitations.…”
Section: Introductionmentioning
confidence: 99%